PENERAPAN MANAJEMEN BALANCE SCORECARD (BSC) PADA PT. BPR NUSUMMA JATENG CABANG BLORA - Ari Kuntardina; Prasto Dwi Wahjono (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study aims to determine the application of Management Balanced Scorecard (BSC) at Rural Bank Nusumma Central Java Branch of Blora. Innovative companies use the scorecard as a strategic management system in managing long-term strategy. Based on research results, it can be concluded that the overall financial perspective has shown good results, although not optimally, performance consumer perspective shows that consumers have a customer satisfaction rate of 73% is located in the Satisfied. The internal process perspective of performance showed improved performance of business services to customers, the better. Performance of growth and learning perspective shows increased employee productivity, retention of employees remain, and the level of employee satisfaction to company policy of 76%